Grundlagen eines soliden und solidarischen Pensionskontensystems - Knell, Markus (Wirtschaft und Gesellschaft, 2016)
There exist two demographic phenomena that pose a challenge for pension systems: the increase in average life expectancy and socio-economic differences in life expectancy. A balanced system has to react to both phenomena such that on the one hand it remains financially stable while on the other hand being constructed in a way that is regarded as fair. In this article I present a proposal how the Austrian, defined-benefit pension account system could be adapted in order to meet these two requirements. The proposal is based on replacement rates that differ both with respect to individual lifetime incomes and over time. I discuss normative principles according to which such a differentiation can be regarded as fair. Furthermore, I sketch the possible practical implementation of the proposal and I compare it to alternative methods like differentiated contributions rates and differentiated closing cash contributions.